Notes on Sumerian Lexicography, I - Civil, M.
1. dum-dam-za; 2. The Reading of ANŠE.KUR.RA; *sisi; 3. úKI.dNANNA = *úmunzur; 4. ki-še-er/ki-šerx(GÌR.BAR) – tuku, Аkk. kišda išû/rašû: 5. IM.DU8 = “dew”.